Hypertrophic osteoarthropathy in a sheep - Hisadora Advincula da Silva Chaves Bom; Givaldo Bom da Silva Filho; Silvio Miguel Castillo Fonseca; Stephanie Carrelo de Lima; Huber Rizzo; Valdir Morais de Almeida; Francisco de Assis Leite Souza; Fábio de Souza Mendonça (Ciência Rural, 2020)
ABSTRACT: This research described the radiological, clinical and pathological aspects of hypertrophic osteoarthropathy in a seven-year-old Santa Inês ram. The main clinical features were lameness of the thoracic and pelvic limbs, rigid, cracking and enlarged of the humeroradial, humeroulnar and tibiofemoral joints, cervical spine stiffness, and severe lordosis of the thoracolumbar vertebrae. Dyspnea, nasal discharge and abdominal breathing were also observed. On radiographic examination of the thoracic and pelvic limbs, osteoarthrosis with the formation of osteophyte bridging, intra-articular calcification and periosteum reaction were observed. At necropsy were reported bilateral osteophytosis in the humeroradial, humeroulnar, tibiofemoral and interphalangeal joints, and fusion of the bodies of thoracic vertebrae T5-13 T6 and T12-T13. Microscopically, extensive areas of fibrosis were observed in the lungs and the affected joints were thickened by well demarcated and perpendicular orientated woven and trabecular bone proliferation in the epiphysis. The periosteum was also expanded by fibrous connective tissue that extended into and between the new proliferated bone. Based on these findings, hypertrophic osteoarthropathy, which is an unusual condition in sheep, was diagnosed.